Inflation and Taxes in a Growing Economy with Debt and Equity Finance - Feldstein, Martin; Green, Jerry; Sheshinski, Eytan (Journal of Political Economy, 1978)
Our tax system was designed for an economy with little or no inflation. The current paper shows that inflation causes capricious changes in the effective rate of tax on capital income and therefore in the real net rate of return that savers receive. This is not only a temporary disequilibrium effect but one which persists in steady-state equilibrium. Unlike earlier papers by Feldstein and by Green and Sheshinski, the current study recognizes that firms finance investment by both debt and equity in a ratio that depends on the tax rates and on the rate of inflation.